The ability of a submaximal cycle ergometer test to detect longitudinal changes in VO2max - Frida Björkman; Örjan Ekblom; Elin Ekblom-Bak; Tony Bohman (BMC, 2021)
Abstract Background The purpose of the present study was to examine the ability of a submaximal cycling test to detect longitudinal changes in maximal oxygen uptake (VO2max) and examine the conformity between changes in measured and estimated VO2max over a time span of 5-8 years. Methods A total of 35 participants (21 men and 14 women), aged 29 to 63 years, performed the Ekblom-Bak (EB) submaximal cycle test for estimation of VO2max and a maximal treadmill running test for direct measurement of VO2max. The baseline tests were conducted between 2009 and 2012, and the follow-up tests were completed 5 to 8 years later. Pearson's coefficient of correlation (r) and paired sample t-test were used to analyse the association between change in measured and estimated VO2max. Random and systematic errors between the measured and estimated VO2max were evaluated using Bland-Altman plots. Repeated measures ANOVA were used to test differences between changes over time. Results There was no significant change in mean measured VO2max between baseline and follow-up (p = 0.91), however large individual variations were noted (− 0.78 to 0.61 L/min). The correlation between individual change in measured and estimated VO2max was r = 0.75 (p < 0.05), and the unstandardised B-coefficient from linear regression modelling was 0.88 (95% CI 0.61 to 1.15), i.e., for each litre of change in estimated VO2max, the measured value had changed 0.88 L. The correlation between baseline and follow-up errors (the difference between estimated-measured VO2max at each occasion) was r = 0.84 (p < 0.05). With regard to the testing procedure, repeated measures ANOVA revealed that there was no significant difference between the group who exercised at the same work rates at baseline and follow-up (n = 25), and those who required a change in work rate (n = 10). Conclusions The EB test detected a change in VO2max with reasonably good precision over a time span of 5-8 years. Further studies are needed to evaluate if the test can be used in clinical populations and in subjects with different medications.